Sensitivity of Multistage Fill Slope Based on Finite Element Model - Bingxiang Yuan; Zihao Li; Zhilei Su; Qingzi Luo; Minjie Chen; Zuqing Zhao (Advances in Civil Engineering)
Based on the strength reduction method, the laws of slope displacement and the changing positions of the sliding surface during the filling process are studied. The model of multistage fill slope is established by the finite element software PLAXIS. The difference is compared between the slope with no reinforcement and with reinforcement under the same working condition. Sensitivity analysis is carried out from two aspects which are internal factors and external factors. The finite element analysis shows that the settlement of the multistage fill slope with no reinforcement is mainly concentrated on the right side of the slope and gradually decreases with the increase of the filling height. The position of the sliding outlet is located at the joint of the first and the second grade of the slope. The effect of the reinforcement on the sliding surface is ideal. It is obvious that the reinforcement can supply the slope with a better position of the sliding surface, which is beneficial to the stability of the slope. The sensitivity analysis shows that unit weight, ratio of slope, and height of each grade are negatively correlated with the safety factor. At the same time, the platform width, cohesion, and internal friction angle are positively correlated with the safety factor. The internal friction angle has the greatest influence on the stability of the slope. Besides, the platform width and the height of each grade should be controlled at about 4 m. The sensitivity analysis provides a reference for the design of the multistage filling slope.